FUNGSI HADIAH DAN HUKUMAN DALAM MEMOTIVASI PERUBAHAN PRILAKU SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Yulia Yulia (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
The purpose of the research was to analyze the use of Reward and punishment in motivating behavior changes of students in the subjects of PAI in SMA Negeri 1 pangkalan Lampam OKI. Results found: The process of implementation of reward and punishment in the learning process of PAI in SMA Negeri 1 Pangkalan Lampam was already effective, the rewards given in the form of a score up to scholarships and the punishments given most effective were by rote of juz amma. This could contribute to give the abundant effect on violation of the students. Rewards and punishments were applied to all students without exception and rewards were given to students also was suitable with the norms of Islamic education. The school also applied the reward and punishment to teachers and staff. Behavior changes of students after application of reward and punishment had experienced the change; it was seen from the reduction in violations, discipline and achievement increased. The functions of reward and punishment in motivating behavior change of students were very effective. Students became more vying in achievement because there were rewards and students were abundant to do mistakes because the existence of punishment, especially on the subjects of PAI